The Song Tau Nduweni by Keroncong Group Titi Laras: A Perspective on Song Form and Marketing Strategy - Lailatus Sa'diyah (Universitas Negeri Surabaya, 2026)
Surabaya is home to many keroncong music groups, one of which is Titi Laras. This group blends traditional keroncong with other musical genres, creating a distinctive musical style. Based on this background, the study addresses two main research questions: (1) What is the management concept of Titi Laras? and (2) What are its marketing strategies?This research employs a qualitative method, utilizing observation, interviews, and documentation techniques. The validity of the data is tested through triangulation, and the data analysis process involves collection, reduction, and presentation of data.The findings indicate that Titi Laras applies the fundamental management functions: planning, organizing, directing, and controlling. Its marketing strategy leverages social media platforms such as YouTube, TikTok, Instagram, and Spotify. This approach has enabled Titi Laras to enhance the quality of its performances.